Bacterias gram negativas, presentes en los conos de gutapercha en las cajas de manipulación de la clínica de adultos III de la facultad de odontología de la Universidad Antonio Nariño (2023)
Endodontics is recognized as the science and art from which a treatment is performed on both the tooth and the apical tissues with the intention of maintaining oral health, in the study of endodontics the study of different variables are fundamental, among which are the study of the microbiota. Due to this condition, the present study intends to analyze the gram-negative agents present in gutta-percha cones in the root canal treatment in the adult clinic III of the faculty of dentistry of the Antonio Nariño University, from an applied methodology that allows to recognize the existence of a contamination of 29% of all the samples, that, although it is a percentage perite recognize the presence of four different bacteria that without proper care can end up affecting the oral and general health of the patient.